An Unusual Case of Ototoxicity with Use of Oral Vancomycin - Umut Gomceli; Srija Vangala; Cosmina Zeana; Paul J. Kelly; Manisha Singh (Case Reports in Infectious Diseases)
Introduction. Systemic absorption of oral vancomycin is poor due to the size of the molecule and its pharmacokinetics. It has an elimination half life of 5–11 hours in patients with normal renal function. We present a rare case of ototoxicity after oral vancomycin administration and detectable serum vancomycin levels 24 hours after cessation of vancomycin. Case Presentation. A 42-year-old woman with a history of hypertension, diabetes mellitus, and previously treated Clostridium difficile colitis presented with abdominal pain and diarrhea for two weeks. Clostridium difficile infection was confirmed by PCR, and at the time of diagnosis and initiation of therapy, the patient had normal renal function. Vancomycin was initiated at a dose of 125 mg po q6h. After the third dose of oral vancomycin, the patient reported new symptoms of lightheadedness, sensations of “buzzing” and whistling of bilateral ears, and decreased perception of hearing described as “clogged ears.” The patient reported to the emergency department the next day due to worsening of these symptoms, and vancomycin dosing was reduced to every 8 hours; however, the patient reported the auditory symptoms persisted. On day three, vancomycin was discontinued with gradual resolution of symptoms over the next 12 hours. On day four, a serum random vancomycin level obtained 24 hours after the last dose was detectable at 2 mcg/dl. Temporal association of the patient’s symptoms and improvement with cessation of therapy along with a detectable vancomycin level indicates systemic absorption of oral vancomycin with subsequent ototoxicity. Discussion. The potential for absorption of oral vancomycin is not well described and is attributed to compromised intestinal epithelium allowing for increased drug absorption. Few studies suggested that oral vancomycin may result in therapeutic or even potentially toxic levels of serum vancomycin in patients with impaired renal function. Ototoxicity may be a transient or permanent side effect of vancomycin therapy and is related to high serum levels. Symptoms usually resolve after decreasing the dose or cessation of vancomycin. No detectable serum vancomycin levels were found in 98% of the patients treated with oral vancomycin in a prospective study. The described case is unusual because despite normal renal function, the patient still developed ototoxicity, and systemic absorption of the drug was confirmed with a measurable vancomycin level approximately 24 hours after the drug was stopped. Additionally, the only other medication prescribed to the patient at the time of vancomycin administration was metformin at a dose of 500 mg po bid which has no known idiosyncratic interactions potentiating adverse side effects to vancomycin. This case reflects that some patients may be more susceptible to increased systemic absorption via the oral route, and the possibility for ototoxicity should be considered and discussed with patients while prescribing oral vancomycin.